Evaluate:
Please refrain from using W|A or any other equivalent softwares.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Put 2 x = t to transform the integral to 6 1 ∫ 0 π / 2 sin t arctan ( 5 sin t ) d t
Define I ( n ) = ∫ 0 π / 2 sin t arctan ( n sin t ) d t
Derivating with respect to n ,
I ′ ( n ) = ∫ 0 π / 2 1 + n 2 sin 2 t 1 d t
= n 2 + 1 1 ∫ 0 π / 2 tan 2 t + n 2 + 1 1 sec 2 t d t
Put tan t = z to get, and use ∫ x 2 + a 2 d x = a 1 arctan ( x / a ) to get
I ′ ( n ) = 2 n 2 + 1 π
Now, integrate both sides with respect to n to get
I ( n ) = 2 π ln ( n + n 2 + 1 ) + c
As I ( 0 ) = ∫ 0 π / 2 sin t arctan ( 0 sin t ) d t = ∫ 0 π / 2 0 d t = 0 , we get c = 0 .
Hence, I ( n ) = 2 π ln ( n + n 2 + 1 )
Replace n = 5 and divide by 6 to get the answer.